1986
DOI: 10.1002/anie.198609601
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide Ion Initiated Reactions Under Phase Transfer Catalysis Conditions: Mechanism and Implications. New Synthetic Methods (62)

Abstract: The development of Phase Transfer Catalysis (PTC) represents a major step forward in the employment of many organic reactions and renders them very convenient and useful processes. These reactions involve the application of nucleophiles in general, anions and bases in particular, in reactions carried out in a water‐organic solvent system. They can be performed both in the laboratory and on an industrial scale. The ease of application of PTC processes is the main reason for their increasing utilization in indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 41 publications
2
65
0
1
Order By: Relevance
“…The quaternary salt, TBAHSO 4 , was used as the catalyst in a basic media (3N NaOH), which increases the rate of the phase transfer as previously reported by Rabinovitz et al [10] and fully observed in our results [6,7]. Also, we evaluated the efficiencies of the derivatization reactions at two temperatures (60 • C and 70 • C) and different reaction times from 30 min to 4 h. The optimal derivatization condition for most of the analytes was incubation for 1-h reaction at 60 • C. After derivatization, the reaction mixtures were cleaned using sorbent-immobilized liquid extraction instead of using formal liquid-liquid extraction coupled with silica gel cleanup, which enabled us to significantly reduce the amount of time required for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The quaternary salt, TBAHSO 4 , was used as the catalyst in a basic media (3N NaOH), which increases the rate of the phase transfer as previously reported by Rabinovitz et al [10] and fully observed in our results [6,7]. Also, we evaluated the efficiencies of the derivatization reactions at two temperatures (60 • C and 70 • C) and different reaction times from 30 min to 4 h. The optimal derivatization condition for most of the analytes was incubation for 1-h reaction at 60 • C. After derivatization, the reaction mixtures were cleaned using sorbent-immobilized liquid extraction instead of using formal liquid-liquid extraction coupled with silica gel cleanup, which enabled us to significantly reduce the amount of time required for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…PTC reactions that use aqueous bases to generate carbanions are termed hydroxide-initiated PTC. 30 The mechanism of hydroxide-initiated PTC reactions is an intensely investigated subject that has been thoroughly reviewed from both a chemical 31 and engineering 32 perspective. Pioneering studies by Makosza 33 and Starks 34 led to two distinct mechanistic descriptions, later termed the interfacial (Makosza) and extraction (Starks) mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The free catalyst can, again, undergo the ion exchange at the interface. Rabinovitz et al [47] reviewed the interfacial mechanism of hydroxide ion initiated alkylation in presence of PTC. In view of the early results and observation, the mechanism for C-arylation of phenylacetonitrle with 1-chloro-4-nitrobenzene under liquid-liquid biphase condition involves the following steps: 1) The organic phase substrate phenyl acetonitrle is deprotonated at the interface by the aqueous phase NaOH and forming an ion-pair [Na …”
Section: Mechanismmentioning
confidence: 99%